Correlation between Limited Education and Transfer of Learning - Thies, Indrani Medhi; Menon, S. Raghu; Cutrell, Ed; Toyama, Kentaro (Information Technologies and International Development, 2012)
One of the greatest challenges in designing applications for developing communities is that potential users may have little or no education. We investigate how limited education correlates with cognitive skills for conceptual abstraction, as required for transfer of learning in video-based skills training. Through a controlled experiment we compared 56 participants from low-income communities in India, split into two groups of 28, based on scores of a textual literacy assessment tool. Group A included participants who passed the test cut-off condition; Group B included those who did not. Participants were then rated for their ability to generalize video instructions on how to use a vacuum cleaner to similar, but not necessarily identical, tasks. Results confirmed that: 1) Both groups faced challenges when a skill required generalization from instructional material; 2) Group A performed better than Group B all-around on this learning task; 3) Diversification of examples within instructions helped Group A participants in transfer of learning, but not Group B participants. We conclude with design recommendations for instructional videos for populations with limited education.